2010
DOI: 10.1088/0004-637x/724/1/748
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of Galactic Anticenter Planetary Nebulae and the Oxygen Abundance Gradient in the Galactic Disk

Abstract: We have obtained spectrophotometric observations of 41 anticenter planetary nebulae (PNe) located in the disk of the Milky Way. Electron temperatures and densities, as well as chemical abundances for He, N, O, Ne, S, Cl, and Ar were determined. Incorporating these results into our existing database of PN abundances yielded a sample of 124 well-observed objects with homogeneously determined abundances extending from 0.9 to 21 kpc in galactocentric distance. We performed a detailed regression analysis which acco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
151
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(173 citation statements)
references
References 60 publications
(91 reference statements)
16
151
6
Order By: Relevance
“…For HII regions (Balser et al 2011), we provide two values: one from the azimuthally averaged gradient (Zhii) and one from the relation established in the azimuthal range which corresponds to the star's galactic longitude (Zhiib). For Planetary nebulae, we use the relation of Henry et al (2010). The O/H and Fe/H determinations give consistent results.…”
Section: Discussionmentioning
confidence: 92%
“…For HII regions (Balser et al 2011), we provide two values: one from the azimuthally averaged gradient (Zhii) and one from the relation established in the azimuthal range which corresponds to the star's galactic longitude (Zhiib). For Planetary nebulae, we use the relation of Henry et al (2010). The O/H and Fe/H determinations give consistent results.…”
Section: Discussionmentioning
confidence: 92%
“…Open cluster measurements (Yong et al 2012;Frinchaboy et al 2013) have found a flattening of the radial gradient at large Galactocentric radii, while observations with Cepheid variables (Luck & Lambert 2011;Lemasle et al 2013) find that the slope does not change in the outer disk. In the inner Galaxy, Henry et al (2010) find that the slope of the radial gradient is shallower than at the solar circle using planetary nebula, but Cepheid observations (Luck & Lambert 2011;Genovali et al 2013) find that the gradient is steepest in the inner Galaxy. These previous studies have generally been limited in sample size to less than a few hundred objects, and generally target objects close to the plane of the Galaxy.…”
Section: Introductionmentioning
confidence: 97%
“…Various tracers have been used including Cepheid variables (e.g., Lemasle et al 2013), planetary nebulae (e.g., Henry et al 2010;Stanghellini & Haywood 2010), H ii regions (e.g., Balser et al 2011), open clusters (e.g., Carrera & Pancino 2011;Frinchaboy et al 2013), B stars (e.g., Daflon & Cunha 2004;Daflon et al 2009), and surveys of main sequence stars (e.g., Cheng et al 2012b for the Sloan Extension for Galactic Understanding and Exploration (SEGUE; Yanny et al 2009) of the Sloan Digital Sky Survey (SDSS; York 2000); Nordström et al 2004 for the GenevaCopenhagen Survey (GCS; Boeche et al 2013) for the Radial Velocity Experiment (Steinmetz et al 2006)). Near the solar circle, the measured amplitude of the Milky Way radial gradient ranges from −0.04 dex kpc −1 in [S/H] in OB stars (Daflon et al 2009) to −0.099 dex kpc −1 in [Fe/H] in main sequence stars between 4 < Gyr < 6 from the GCS (Nordström et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties in 12+log(X/H) were adjusted using a scaling factor f (X ) until the fit accounted for all of the scatter in the data. This optimized fit yields χ 2 = 1 (see Henry et al 2010). Fits and resultant abundance gradients are shown in Table 1.…”
Section: Introduction Data and Analysismentioning
confidence: 99%